2019
DOI: 10.17161/jis.v12i1.11565
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring Characteristics and Functions Important to Men and Women within Intercollegiate Athletic Administration

Abstract: Female athletic administrators were asked about the role of mentoring in their careers as women while male athletic administrators were asked about the role of mentoring in their careers as men working in intercollegiate athletic administration.  The researchers gathered and compared information on mentor characteristics as well as career and psychosocial benefits of having a mentor. Participants were 518 female and 778 male athletic administrators working at NCAA Division I, II, and IIII, NAIA, NCCAA, and NJC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Most of the study's respondents pointed to a general lack of upward mobility across ticket sales departments, but the underrepresented groups specifically highlighted a lack of mentorship. This is supported by prior literature on mentorship and career progression of underrepresented groups in the sport industry, which highlight existing gaps (Hancock and Hums, 2016;Sattler et al, 2018;Bower and Hums, 2013). From a strategic human resource perspective, Woo et al (2018) recommends that in addition to creating leadership opportunities for minority populations, managers should create shadowing opportunities for entry-level employers to maintain a diverse workforce.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Most of the study's respondents pointed to a general lack of upward mobility across ticket sales departments, but the underrepresented groups specifically highlighted a lack of mentorship. This is supported by prior literature on mentorship and career progression of underrepresented groups in the sport industry, which highlight existing gaps (Hancock and Hums, 2016;Sattler et al, 2018;Bower and Hums, 2013). From a strategic human resource perspective, Woo et al (2018) recommends that in addition to creating leadership opportunities for minority populations, managers should create shadowing opportunities for entry-level employers to maintain a diverse workforce.…”
Section: Discussionmentioning
confidence: 85%
“…In their study of female sales managers' experiences across professional sport organizations, Sattler et al (2018) found just over half (61.4%) of female sales managers could identify a workplace mentor, and of that, less than a third (29.7%) identified having another woman as their mentor. Bower and Hums (2013) noted the lack of female administrators in intercollegiate athletics could lead to barriers for women entering the field. Specifically, they noted a lack of mentorship as one of those barriers.…”
Section: The Importance Of Ticket Sales In Marketingmentioning
confidence: 99%
“…More important, female mentors are needed to provide the psychosocial aspects of mentoring. However, considering the important role that both male and female academics play in providing wider qualities of an academic role to the mentee (Obers 2014) and the importance of the level of satisfaction reported by mentees in mentoring relationships (Ragins & Cotton 1999), it would be better to arrange for cross gender mentoring relationship involving male and female mentors for a female mentee as suggested by Bower (2013). Perhaps, the arrangement would cater for career and psychosocial development of the young female academics returning from abroad to positions of leadership.…”
Section: Discussionmentioning
confidence: 99%
“…However, women face barriers of finding female mentors in higher education due to a shortage of women in leadership positions. Bower (2013), recommends having cross gender mentoring so that one provides career support and another on psycho social support. As Bower states; "I think being mentored by a man and a woman is an advantage because each has a different perspective".…”
Section: Mentoring Women In Higher Educationmentioning
confidence: 99%
“…have demonstrated that the widespread implementation of mentorship programs can effectively facilitate professional development and increase career satisfaction. Imparting the knowledge and skills related to the organization and the position improves employee competency, fulfills their psychological contract, and promotes the future of their career, thereby enhancing their work performance and the performance and competitiveness of the enterprise (Bower et al, 2019;Chen, 2014;Huang et al, 2016). Traditional mentorship refers to the mainstream mentorship model used by various enterprises and organizations in Taiwan and involves experienced employees imparting knowledge unidirectionally to inexperienced employees.…”
mentioning
confidence: 99%